Advance Exergo-Economic Analysis of a Waste Heat Recovery System Using ORC for a Bottoming Natural Gas Engine (2020)
This manuscript presents an advanced exergo-economic analysis of a waste heat recovery system based on the organic Rankine cycle from the exhaust gases of an internal combustion engine. Different operating conditions were established in order to find the exergy destroyed values in the components and the desegregation of them, as well as the rate of fuel exergy, product exergy, and loss exergy. The component with the highest exergy destroyed values was heat exchanger 1, which is a shell and tube equipment with the highest mean temperature difference in the thermal cycle. However, the values of the fuel cost rate (47.85 USD/GJ) and the product cost rate (197.65 USD/GJ) revealed the organic fluid pump (pump 2) as the device with the main thermo-economic opportunity of improvement, with an exergo-economic factor greater than 91%. In addition, the component with the highest investment costs was the heat exchanger 1 with a value of 2.769 USD/h, which means advanced exergo-economic analysis is a powerful method to identify the correct allocation of the irreversibility and highest cost, and the real potential for improvement is not linked to the interaction between components but to the same component being studied.